The Use of Picture-Based English Materials to Improve Students’ Vocabulary Mastery for States Elementary Schools - Muhsinin; Arif Rahman; Ahmad Javed Hassan; Said Malika Tridane Manu (Journal of Language and Literature Studies, 2024)
The research aimed to find out improving students’ vocabulary mastery by using pictures. This research was conducted by using Classroom Action Research (CAR). The subject of this research was grade III of MIN 2 Mataram 2023/2024 academic year which consisted of 35 students consisting of 20 female and 15 male. The object of this research was to improve the students’ vocabulary mastery through pictures. This researcher was conducted in two cycles which each consists’ of planning, acting, observing,  and  reflecting.  The  data  were   gathered  through  qualitative  and quantitative  data.  The  qualitative  data  were  gained  by  analyzing  the  test  and observation  result.  Then,  quantitative  data  were  obtained  from  the  students’ vocabulary score of pre-test and post-test. Based on the result of this research showed that there was a development on the students’ vocabulary mastery, it can be seen if the score of students who got >73 grew up. It can be seen from the mean score of pre-test were 61.31, the mean score of post-test 1 was 72.39, and the mean score of pot-test cycle 2 was 82.39. In addition, there were 12 students (31,57%) who passed Minimum Mastery Criterion (KKM) in the post test of cycle 1. Meanwhile, in the cycle 2, there were 23 students (89, 4%) who passed Minimum Mastery Criterion (KKM). so the criteria of success was achieved. Then, from the result of observation it showed that there was improvement of positive responses in the teaching-learning process of vocabulary through pictures as media and it also showed that the students were motivated in teaching-learning process during the implementation of pictures.